(untitled) (Географический вестник=Geographical bulletin, 2017)
Рассматриваются особенности переформирования береговой зоны нижнего бьефа Камского гидроузла в черте г. Перми. Приведена дифференциация ключевого участка берега по типу переформирования. GEODYNAMICS IN LOWER POOL OF THE KAMA HYDROELECTRIC POWER STATION (RIGHT BANK OF KAMA RIVER IN PERM) The differentiation of a coastal zone in lower pool of Kama hydroelectric power station in Perm city was organized as a rearrangement. As a result, the following types of coast have been allocated: abrasion-erosion-collapse, abrasion-erosion-landslide, abrasion-erosion-gully, coast break off of a slope, coast hydration aerations and phytogenous destruction, residential coast with handicraft coast protection constructions, artificial beaches, technogenic coast.